2003
DOI: 10.1029/2002jc001674
|View full text |Cite
|
Sign up to set email alerts
|

Export pathways for river discharged fresh water in the northern Gulf of Mexico

Abstract: [1] A numerical simulation of the Gulf of Mexico (GoM) using the Navy Coastal Ocean Model (NCOM) is used to identify the pathways by which fresh water discharged by major rivers in the northern Gulf is exported away from the region. The NCOM, a new primitive equation ocean model with a hybrid sigma/geopotential level vertical coordinate, is described along with its application to the GoM region. Trajectories from surface drifters are analyzed to show evidence of the seasonally shifting alongshore and crossshel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
149
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(177 citation statements)
references
References 45 publications
20
149
3
Order By: Relevance
“…The concept of varying source terms that differ in stoichiometry was reported by Frigstad et al (2011), who found that the average C / N ratio of suspended particulate organic material (POM) in the Norwegian shelf was the combined result of that due to autotrophs and heterotrophs (the former being higher than Redfield). Differences in uptake by various biological communities may explain observed temporal and spatial differences in stoichiometry (Pahlow and Riebesell, 2000;Li et al, 2000;Li and Peng, 2002). For example, C / N remineralization ratios of 5.48 were reported in the Atlantic Ocean (Li et al, 2000) compared to 4.6 ± 0.6 between latitudes 45-5 • N (Li and Peng, 2002).…”
Section: Stoichiometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of varying source terms that differ in stoichiometry was reported by Frigstad et al (2011), who found that the average C / N ratio of suspended particulate organic material (POM) in the Norwegian shelf was the combined result of that due to autotrophs and heterotrophs (the former being higher than Redfield). Differences in uptake by various biological communities may explain observed temporal and spatial differences in stoichiometry (Pahlow and Riebesell, 2000;Li et al, 2000;Li and Peng, 2002). For example, C / N remineralization ratios of 5.48 were reported in the Atlantic Ocean (Li et al, 2000) compared to 4.6 ± 0.6 between latitudes 45-5 • N (Li and Peng, 2002).…”
Section: Stoichiometrymentioning
confidence: 99%
“…Such strong tidal exchange also introduces Mississippi River-influenced shelf water into this estuary (Li et al, 2011). The dominant coastal current on the Louisiana shelf generally flows to the west, but a clockwise eddy occurs in the Louisiana Bight adjacent to the northwest of the Mississippi River birdfoot delta (Morey et al, 2003;Walker et al, 2005).…”
Section: Site Descriptionmentioning
confidence: 99%
“…These later models generally have better resolutions (with one or two exceptions). Apart from Morey et al [2003] and Zavala-Hidalgo et al [2003b], who used a domain similar to Dietrich and Lin's [994] and hence specify essentially the total Yucatan transport (see below), others' domains include the entire Caribbean Sea. Mooers and Maul's POM (at 20 km resolution and 5 vertical sigma levels; C smag = 0.05) domain is similar to that of Sturges et al [993], including also the Caribbean Sea.…”
Section: Loop Current and Eddies In The Earlymentioning
confidence: 99%
“…The ocean model used for this study is the NCOM as described in Martin (2000), with some improvements as described in Morey et al (2003) and Barron et al (2006). This is a hydrostatic model, which is similar in its physics and numerics to the Princeton Ocean Model (POM) (Blumberg and Mellor, 1987), but uses an implicit treatment of the free surface and a hybrid vertical grid with sigma coordinates in the upper layers and (optionally) level coordinates below a user-specified depth.…”
Section: Coastal Model and Configurationmentioning
confidence: 99%